OVERVIEW OF PREPAREDNESS ATTITUDES IN FIRE DISASTER MANAGEMENT AMONG CORRECTIONAL OFFICERS AT POHUWATO CORRECTIONAL FACILITY - Mei Lina Hesti Dwi Saputri; Zulkifli B Pomalango; Ibrahim Suleman (PT. Jurnal Center Indonesia Publisher, 2025)
Fire incidents continue to be a major concern. Data from the International Association of Fire and Rescue Services (CTIF) in 2022, recorded > 1.3 million fire incidents worldwide each year, causing more than 15,000 deaths and economic losses. Fire disasters are one of the serious threats in various environments, including Correctional Institutions (Lapas). Prisons have a high potential risk of fire due to various factors, such as the use of unsafe electrical equipment, overcrowding, lack of adequate fire fighting facilities and riots that lead to fires. The purpose of the study was to determine the picture of the attitude of preparedness related to fire disaster management among correctional officers at Pohuwato Prison. The type of quantitative descriptive research , the population of all Correctional Officers at Pohuwato Prison recorded in 2024 was 71 people. Sampling used the Non-Probability Sampling method with the Purposive Sampling technique . The technique was chosen based on certain considerations according to the research criteria. A sample of 59 respondents was obtained. The single variable analyzed was related to the attitude of preparedness. Data were collected through questionnaires and analyzed using reliability and normality tests . The results of the study showed a picture of the attitude of preparedness of correctional officers with a sufficient category of 56 respondents (94.9%). It was concluded that the attitude of preparedness of correctional officers was still sufficient and there was a need for counseling or training related to fire disaster management at Pohuwato Prison.